ANALYSIS OF OIL PALM AND RUBBER PRODUCTION TO GROSS DOMESTIC PRODUCT OF TEN DISTRICTS IN WEST KALIMANTAN BY PANEL REGRESSION - Sulistianingsih, Evy; Kiftiah, Mariatul; Rosadi, Dedi; Wahyuni, Heni (Journal of Technology Management and Business, 2018)
West Kalimantan is a province in Indonesia that has a prominent role as oil palm and rubber producer. However, it is inevitable that as oil palm and rubber production plantation have developed, environmental and social problems as well happened nearly the plantation areas. For that reason, this research was conducted to analyse the relationship of oil palm and rubber production to the welfare of inhabitants in ten districts in West Kalimantan, namely Sanggau, Sintang, Sambas, Ketapang, Bengkayang, Landak, Kapuas Hulu, Melawi, Sekadau and Singkawang. The welfare of the inhabitants in this case was measured by Gross Domestic Product of every districts. According to the result, it can be deduced that Fixed Effect Model with adjusted determination-coefficient 0,76,Â  is the best model to analyse this case. In addition, the research also concludes that oil palm and rubber production are statistically significant to GDP of the districts. So that, even though oil palm and rubber production tend to give negative impact to the environment but the result of this research shows that oil palm and rubber production donate positive influence to increase the welfare of the inhabitants.Keywords: Longitudinal, Breusch-Pagan, Cross-Section Weight